Eficiência do calcário calcítico e dolomítico na correção da acidez de solo sob plantio direto - Holzschuh, Marquel Jonas (2007)
Liming is used to decrease soil acidity and increase exchangeable calcium and magnesium levels, but it may impaired calcium and magnesium ratios with continuous use of dolomitic or calcitic lime. The aim of this work is to evaluate the efficiency of different proportions of calcitic and dolomitic lime on soil acidity neutralization, evaluated by crop yields and in the Ca and Mg levels in plant. Four experiments were carried out in different physiographic regions of Rio Grande do Sul in October 2004 and carried on until March 2006, with two soybean (Glycine max L. Merril) and black oat (Avena strigosa Schieb)crops. The treatments were constituted by the following calcitic and dolomitic lime proportions: control without lime; 100% calcitic; 75% calcitic and 25% dolomitic; 50% calcitic and 50% dolomitic; 25% calcitic and 75% dolomitic and 100% dolomitic, arranged in randomized block design with subplot with four replications, being the main plots constituted by surface and incorporated methods and the secondary plots were submitted to the lime proportions. The black oat dry matter yield, the soybean grains yield and the levels of Ca and Mg in the soybean and black oat tissue were evaluated. In soil samples collected in layers from 0 5; 5 10; 10 -15; 15 20; 0 10 e 0 - 20 cm, the Ca, Mg e Al, exchangeable levels, pH H2O, SMP index, bases saturation and the Ca/Mg ratios were determined. All the variants were submitted to the variance analysis at 5% and when significant, the means were compared by the Tukey test at 5%. The results show that the Ca/Mg ratio and the lime application methods did not have influenced in the soybean and black oat yield. The Ca and Mg levels in the tissue were not influenced by the Ca/Mg ratios. The acidity neutralization, the exchangeable Al neutralization, the increasing of the Ca and Mg levels and the base saturation only occurred in the layer of 0-5 cm on the surface application and until the layer of 10-15 cm in the incorporated application.